2015
DOI: 10.1136/annrheumdis-2015-eular.1220
|View full text |Cite
|
Sign up to set email alerts
|

FRI0128 A Phase III Randomised, Double-Blind Clinical Study Comparing SB4, An Etanercept Biosimilar, With Etanercept Reference Product (Enbrel®) in Patients with Moderate to Severe Rheumatoid Arthritis Despite Methotrexate Therapy (24-Week Results)

Abstract: BackgroundSB4 is a biologic agent developed as a biosimilar of the etanercept reference product (ETN). Etanercept is approved for treatment of rheumatoid arthritis (RA), juvenile idiopathic arthritis, psoriatic arthritis, axial spondyloarthritis, plaque psoriasis, and paediatric plaque psoriasis in the EU.ObjectivesTo compare the efficacy, safety, and immunogenicity of SB4 with ETN in patients with moderate to severe RA despite methotrexate (MTX) treatment.MethodsPatients with moderate to severe RA despite MTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…S2). The modified Downs and Black instrument was used to assess the quality of the 22 identified abstracts for original studies [39, 63–83], with scores of fair quality (3–4) for four studies [39, 66, 70, 76], good quality (5–8) for seven studies [63, 65, 67, 68, 73, 77, 79], and excellent quality (9–12) for 11 studies [64, 69, 71, 72, 74, 75, 78, 80–83] (ESM Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…S2). The modified Downs and Black instrument was used to assess the quality of the 22 identified abstracts for original studies [39, 63–83], with scores of fair quality (3–4) for four studies [39, 66, 70, 76], good quality (5–8) for seven studies [63, 65, 67, 68, 73, 77, 79], and excellent quality (9–12) for 11 studies [64, 69, 71, 72, 74, 75, 78, 80–83] (ESM Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that this finding could possibly be due to differences in the formulation; in contrast to etanercept, SB4 does not contain L-arginine and the needle shield does not contain natural latex. Although the finding was supported by the 52 week data,31 the European Medicines Agency concluded that it likely occurred by chance 28…”
Section: Considering Patient Managementmentioning
confidence: 92%
“…Serious infections were reported in 0.3% and 1.7%, respectively, and malignancies in 1.3% and 0.3% 9. One interesting difference was in injection site reactions, which were reported in 3.7% of patients taking SB4% and 17.5% of those taking Enbrel.…”
Section: Considering Clinical Data For Approved Biosimilarsmentioning
confidence: 97%
“…This was a typical example of a biosimilar study, with a 52 week randomised double blind period followed by an open label extension period up to week 100 in which all patients received SB4 and methotrexate allowing evaluation of a single switch from a bio-originator to the biosimilar 9. The double blind period included 596 patients, but the extension period was carried out only in Poland and the Czech Republic and included 245 patients 10.…”
Section: Considering Clinical Data For Approved Biosimilarsmentioning
confidence: 99%
See 1 more Smart Citation